2008
DOI: 10.1063/1.3021055
|View full text |Cite
|
Sign up to set email alerts
|

Direct assessment of vorticity alignment with local and nonlocal strain rates in turbulent flows

Abstract: A direct Biot-Savart integration is used to decompose the strain rate into its local and nonlocal constituents, allowing the vorticity alignment with the local and nonlocal strain rate eigenvectors to be investigated. These strain rate tensor constituents are evaluated in a turbulent flow using data from highly-resolved direct numerical simulations. While the vorticity aligns preferentially with the intermediate eigenvector of the combined strain rate, as has been observed previously, the present results for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 14 publications
12
69
0
Order By: Relevance
“…The picture of the cascade of TKE described by Leung et al [30] is based upon the vorticity stretching term being largely fed by the alignment of the small-scale (local) vorticity vector with the extensive strain rate of the large-scale (or background in the terminology of Hamlington et al [26]) strain field. Regions for which this alignment is |e 1 ·ω| 0.8 provide the majority of the overall positive contribution to ω i s ij ω j and are thus responsible for the transfer of turbulent kinetic energy from large scales to smaller ones [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The picture of the cascade of TKE described by Leung et al [30] is based upon the vorticity stretching term being largely fed by the alignment of the small-scale (local) vorticity vector with the extensive strain rate of the large-scale (or background in the terminology of Hamlington et al [26]) strain field. Regions for which this alignment is |e 1 ·ω| 0.8 provide the majority of the overall positive contribution to ω i s ij ω j and are thus responsible for the transfer of turbulent kinetic energy from large scales to smaller ones [30].…”
Section: Resultsmentioning
confidence: 99%
“…However, Buxton and Ganapathisubramani [24] observed that the alignment preference between ω and e 1 determines the sign of ω i s ij ω j , with parallel alignment favored for concurrent ω i s ij ω j > 0 and perpendicular alignment favored for ω i s ij ω j < 0. Subsequently, the commonly reported tendency for |e 2 ·ω| ≈ 1 has been explained by the preferential alignment between the vorticity vector and the local intermediate strain-rate eigenvector, particularly in regions of high enstrophy [25], while ω preferentially aligns with the extensive eigenvector of the background strain field [26]. The preferential alignment of the vorticity vector, filtered at a length scale of the characteristic diameter of the high-enstrophy worms [27][28][29], with the large-scale extensive strain-rate eigenvector has been confirmed by Leung et al [30].…”
Section: Introductionmentioning
confidence: 99%
“…Jiménez 6 offered another explanation for the alignment using a kinematic model and attributed it to purely kinematic effects. There have been many more studies about the vorticity alignment, [7][8][9][10][11][12][13] considering various flows like isotropic turbulence, turbulent channel flow (TCF), turbulent boundary layer (TBL), atmospheric turbulence, and magnetohydrodynamic turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…The alignment properties between the rotation directionê ω and the stretching directionê i at the same time have been investigated for the true velocity gradient tensor [22][23][24][25][26][27][28][29] . On the basis of the intuitive notion that stretching is strongest in the directionê 1 , it was expected that there would be a strong alignment ofê ω witĥ e 1 .…”
mentioning
confidence: 99%
“…Thus, the alignment with the initially strongest stretching direction is a dynamical process: not surprisingly, the alignment betweenê ω (t ) andê 1 (0) builds up over time. Understanding the alignment properties betweenê ω and the eigenvectors of the strainê 1 at equal time (Eulerian point of view) requires a proper description of the rotation of the eigenvectors (ê 1 (t ),ê 2 (t ),ê 3 (t )), which is affected by nonlocal (pressure) effects 28 . The time of decorrelation between the direction ofê 1 (t ) andê 1 (0) is found to be on the order of 0.2t 0 , comparable to the time of alignment ofê ω (t ) andê 1 (0), thus explaining the lack of observed alignment between e ω (t ) andê 1 (t ).…”
mentioning
confidence: 99%